Peningkatan Profesionalisme Guru Dalam Proses Pembelajaran Melalui Supervisi KBM - Budi Budi (JURNAL PENA EDUKASI, 2018)
Abstract: The purpose of this study aims to improve teacher sprofesionalisme through supervision activities of KBM in Elementary School 057228 Petani Jaya district Sei Lepan. The results showed teacher professionalism in learning planning at SD Negeri 057228 Petani Jaya sub-district of Sei Lepan after supervision of teaching and learning activity through class visit in good category. This can be proven by the results of the assessment of learning planning in the first cycle reached an average score of 71.35 included in either category, then in cycle II reached an average value of 83.70 included in either category. Improvement of teacher ability can be proved from result of pre-cycle pre-cycle appraisal show average 68,82 and in cycle I increased by 11,96% with average value 80,78, then in cycle II increase again equal to 10,38% to 91.17 with very good category. Improvement of teachers ability in pre-learning / learning planning is also followed by the improvement of teachers' ability in implementing learning in the first cycle reached a value of 71.35 and in the second cycle reached an average value of 83.70, then an increase of 12.35%. Keyword: supervision, learning activities Abstrak: Tujuannya penelitian ini bertujuan untuk meningkatkan sprofesionalisme guru melalui kegiatan supervisi KBM di SD Negeri 057228 Petani Jaya kecamatan Sei Lepan. Hasil penelitian menunjukkan Profesionalisme guru dalam perencanaan pembelajaran di SD Negeri 057228 Petani Jaya kecamatan Sei Lepan setelah supervisi kegiatan belajar mengajar melalui kunjungan kelas dalam kategori baik. Hal ini dapat dibuktikan dengan melalui hasil penilaian perencanaan pembelajaran pada siklus I mencapai nilai rata-rata 71,35 termasuk dalam kategori baik, kemudian pada siklus II mencapai nilai rata-rata 83,70 termasuk dalam kategori baik. Peningkatan kemampuan guru tersebut dapat dibuktikan dari hasil penilaian pra pembelajaran pra siklus menunjukkan rata-rata 68,82 dan pada siklus I meningkat sebesar 11,96% dengan nilai rata-rata 80,78, kemudian pada siklus II meningkat lagi sebesar 10,38% menjadi 91,17 dengan kategori sangat baik. Peningkatan kemampuan guru dalam pra pembelajaran/perencanaan pembelajaran tersebut sekaligus diikuti dengan peningkatan kemampuan guru dalam melaksanakan pembelajaran pada siklus I mencapai nilai sebesar 71,35 dan pada siklus II mencapai nilai rata-rata sebesar 83,70, maka terjadi peningkatan sebesar 12,35%. Kata kunci: supervisi, kegiatan pembelajaran